Electron Microscopic Analysis of Viral Impact on Human Cell Growth and Reproduction - Asim Ismael, Mohammed (American Journal of Bioscience and Clinical Integrity, 2025)
Viruses are microscopic entities that significantly impact human health by infecting host cells and disrupting their normal functions. This study aims to investigate the effects of various viruses, including Influenza virus, Coronavirus, and Herpesvirus, on the growth and reproduction of human cells. Using electron microscopy (EM) techniques, the research will examine cellular structural changes in human epithelial and immune cells upon viral infection. The study will focus on identifying the specific alterations in cellular morphology, the impact on cell division, and potential genetic changes associated with viral replication. By comparing infected cells with uninfected control groups, the research seeks to reveal differences in cellular responses to various viral infections. The results are expected to provide valuable insights into the molecular mechanisms of viral pathogenesis, offering potential targets for therapeutic intervention. This research could lead to improved strategies for preventing and treating viral diseases by identifying novel antiviral targets and enhancing the effectiveness of current treatment protocols.